Strategies of the One-Stop Investment and Integrated Services Office to Increase Investment in Kaur Regency - Apriyanti, Yossi; Soleh , Ahmad; Febliansa , M Rahman (Journal of Accounting and Management, 2025)
This research was motivated by the importance of the role of investment in supporting regional economic development, especially in Kaur Regency. Although the central government had issued various policies to encourage investment, in reality investment in this region still faces various obstacles such as less than optimal promotional strategies, minimal digitalization of services, and weak cross-sector coordination. Therefore, this study aims to analyze the strategies implemented by the Kaur Regency Investment and One-Stop Integrated Service Office (DPMPTSP) in increasing investment, as well as identifying supporting and inhibiting factors in its implementation. This study uses a qualitative method with a field research approach. Data collection techniques are carried out through in-depth interviews, direct observation, and documentation and secondary data from related agencies. Informants in this study consisted of the head of the office, investment staff, and investors. The data analysis technique uses the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The selection of informants was carried out by purposive sampling with certain criteria. The results of the study indicate that the DPMPTSP strategy in increasing investment includes simplifying licensing through OSS, compiling regional potential maps, active promotion in various forums, providing incentives, and cross-sector synergy. However, this strategy is not yet fully optimal because there are still obstacles such as inadequate infrastructure, limited internet networks, and low digital literacy in the community. The conclusion of this study is that the DPMPTSP strategy has been running in the right direction, but requires additional support from various parties. The suggestions given include the need to strengthen the digital system, local HR training, and periodic evaluation of the strategies implemented.